Technological improvements in energetic efficiency and sustainability in existing combined-cycle gas turbine (CCGT) power plants. (1st August 2018) - Colmenar-Santos, Antonio; Gómez-Camazón, David; Rosales-Asensio, Enrique; Blanes-Peiró, Jorge-Juan
Graphical abstract: Highlights: CCGT partially regenerative with solar hybridization maintences the global efficiency like CCGT. Recuperation effectiveness is fundamental factor calculation of the regenerator. Emissions-fuel consumption decrease considerably with partial regeneration. Thermal efficiency obtained in new CCGT hybridized is higher than conventional solar technology. Abstract: Data from an existing combined-cycle gas turbine (CCGT) power plant are used to create a computer simulation to allow efficiency and emission calculations, simulation and assessing improvements that apply partial regeneration with solar hybridization. The proposed amendments to this triple-pressure steam-reheat combined cycle (CCC3PR ) with 400 MW of net power incorporates a regenerator and thermal energy, from a source of renewable solar energy up to 50 MW, in order to reduce the energy loss in the gas turbine. The calculation and simulation models were created using Visual Basic code. Regeneration and solar hybridization were found to contribute to increasing efficiencies of around 2.25% to 3.29% depending on the loading point. The reduction of gas consumption was between 6.25% and 9.45% and the overall cycle efficiency loss is minimal due to hybridization. There was a loss of the net power of the new cycle but it is considerably lower if than heat from a renewable source is supplied to the cycle. This net power loss has an average value of 7.5% with regeneration only and of 1% with regeneration and hybridization. The reduction of fuel consumption is significant which could result in saving approximately 4 million €/year. Partial regeneration in the gas turbine and solar thermal power in the existing CCGTs provide an interesting possibility for reducing emissions (by 26, 167 t/year). In conclusion, partial regeneration with solar hybridization provides an interesting and proven possibility to increase performance and efficiency whilst reducing emissions from the existing CCC3PR .